Deflationism about Truth-Directedness - LUCA ZANETTI (Manuscrito, 2023)
Abstract Contemporary views of truth-directedness endorse what I shall call the Common-Element Argument. According to this argument, there is something in common between judgment and other attitudes like assumption and imagination: they all regard their contents as true. Since this regarding-as-true feature is not distinctive of judgment - the argument goes - it can’t explain its truth-directedness. On this ground, theorists have been motivated to endorse an inflationary view that tries to capture truth-directedness by appealing to some further feature: intentions, second-order representations, sub-personal mechanisms, or subjugation to norms are the most discussed candidates for fulfilling this role. In this paper I will argue that the Common-Element Argument is unsound. It rests on a false premise, namely that there is some common element such as a regarding-as-true component between judgment and other cognitive attitudes. I shall reject Velleman’s and Railton’s defenses of the Common-Element-Argument. Then I will discuss three influential inflationary accounts of truth-directedness: Railton’s account, Velleman’s teleological account, and Shah and Velleman’s conceptualist account. I shall argue that they all face a phenomenological and an explanatory challenge. Finally, I shall sketch a deflationary view of truth-directedness that evades these challenges.